2021
DOI: 10.1371/journal.pgen.1009542
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide proximity between RNA polymerase and DNA topoisomerase I supports transcription in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a major cause of disease and death that develops resistance to multiple antibiotics. DNA topoisomerase I (TopoI) is a novel pneumococcal drug target. TopoI is the sole type-I pneumococcal topoisomerase that regulates supercoiling homeostasis in this bacterium. In this study, a direct in vitro interaction between TopoI and RNA polymerase (RNAP) was detected by surface plasmon resonance. To understand the interplay between transcription and supercoiling regulation in vivo, genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 50 publications
8
28
1
Order By: Relevance
“…We find the model to account for our experimental data only when TopoI and gyrase are allowed to act specifically. In line with previous works on gyrase [30, 50] and TopoI [33, 50, 51] in various bacteria, including E. coli , our results thus demonstrate that these topoisomerases are essential facilitators of transcription. Our analysis further reveals that the production rate of supercoils is lower for TopoI than for gyrase.…”
Section: Discussionsupporting
confidence: 93%
“…We find the model to account for our experimental data only when TopoI and gyrase are allowed to act specifically. In line with previous works on gyrase [30, 50] and TopoI [33, 50, 51] in various bacteria, including E. coli , our results thus demonstrate that these topoisomerases are essential facilitators of transcription. Our analysis further reveals that the production rate of supercoils is lower for TopoI than for gyrase.…”
Section: Discussionsupporting
confidence: 93%
“…Since CTD does not influence transcription elongation, the results support the existence of an RNAP:EcTopoI complex that is formed during transcription initiation and persists during transcription elongation in vivo. In contrast to E. coli, enrichment of streptococcal SpTopoI is abolished by Rif, possibly indicating a distinct mechanism of RNAP:TopoI interaction (Ferrandiz, Hernandez and de la Campa, 2021).…”
Section: Ectopoi Interacts With Rnap In Vivomentioning
confidence: 90%
“…Streptococcus pneumoniae (Ferrandiz, Hernandez and de la Campa, 2021). It was hypothesized that association with RNAP enables TopoI to rapidly relax negative DNA supercoils forming behind the elongating RNAP, thereby preventing the R-loops formation (Cheng et al, 2003;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topo I has an essential role in supporting transcription in S. pneumonia e. We have shown that Topo I and RNA polymerase physically interact in vitro and colocalize at gene promoters in vivo. Binding of each of these enzymes to promoters was prevented by the specific inhibition of the other enzyme, either by rifampicin (RNA polymerase) or by SCN (Topo I), supporting a role for Topo I in RNA polymerase transcription [ 50 ]. These results allowed envisaging SCN as a new drug for the treatment of diseases caused by infection with multi-drug resistant strains of S. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%